MENGHADAPI TANTANGAN KEAMANAN SIBER PADA INFRASTRUKTUR KRITIS: SOLUSI HUKUM DAN ETIKA - Ismail Darmawan; Muharman Lubis (Al-Adl : Jurnal Hukum, 2026)
In an increasingly advanced digital era, critical infrastructure underpins numerous aspects of human life, including energy, transportation, communications, and healthcare services. This paper delineates the principal challenges confronting cybersecurity in critical infrastructure, encompassing technological vulnerabilities, insufficient human resources, and inadequate regulatory frameworks. The research methodology involves an examination of applicable legislative regimes, with particular attention to Indonesia’s Electronic Information and Transactions Law (Undang-Undang Informasi dan Transaksi Elektronik/UU ITE) and the European Union’s General Data Protection Regulation (GDPR). The findings indicate that, although existing legal frameworks provide a robust foundation for combating cybercrime, regulatory modifications and enhancements remain necessary to address evolving threats. The study underscores the importance of collaboration between the public and private sectors in formulating effective cybersecurity strategies. It concludes that safeguarding critical infrastructure must be accorded priority and that an ethical approach to cybersecurity is essential for sustaining public trust.